Quantitative Assay of Arsenic in Experimentally Intoxicated Guinea Pigs - Dinesh Kumar; A.K. Srivastava and Sanjiv Kumar (Veterinary World, 2010)
The present investigation was undertaken with an attempt to generate information pertaining to the assessment of arsenic residues in the vital organs like liver, lungs kidneys along with blood and hair as biomarker of chronic arsenic exposure using guinea pigs as experimental animal. For this purpose the guinea pigs were divided into two groups having 5 animals in each group. Group I animals were fed 1% of Arsenic trioxide @ 1 mg/kg body weight through oral gavages daily for 90 days to produce chronic toxicity. Estimation of arsenic residue was carried out on 90th day post administration. In the present study chronic exposure to arsenic resulted in significant enhancement of arsenic residues in the blood, hair, liver, lungs and kidneys with mean values of 57.18, 333.71, 331.96, 95.8 ppb and 272.95 in guinea pigs of chronic toxicity as compared to 3.47, 14.02, 12.94, 2.56 and 5.56 ppb in control, respectively. [Veterinary World 2010; 3(10.000): 463-465]